Second-Order Nonlinear Analysis of Steel Tapered Beams Subjected to Span Loading. (13th March 2014) - Hadidi, Ali; Farahmand Azar, Bahman; Zonouzi Marand, Hossein
Abstract : A second-order elastic analysis of tapered steel members with I-shaped sections subjected to span distributed and concentrated loadings is developed. Fixed end forces and moments as well as exact stiffness matrix of tapered Timoshenko-Euler beam are obtained with exact geometrical properties of sections. The simultaneous action of bending moment, shear, and axial force including P − δ effects is also considered in the analysis. A computer code has been developed in MATLAB software using a power series method to solve governing second-order differential equation of equilibrium with variable coefficients for beams with distributed span loading. A generalized matrix condensation technique is then utilized for analysis of beams with concentrated span loadings. The accuracy and efficiency of the results of the proposed method are verified through comparing them to those obtained from other approaches such as finite element methods, which indicates the robustness and time saving of this method even for large scale frames with tapered members.